Zakat Perniagaan Karet Di Kecamatan Bajubang Kabupaten Batang Hari Ditinjau Dari Hukum Islam - Duwinta Primania; Johni Najwan (Universitas Jambi, Fakultas Hukum, 2020)
In Bajubang District, the population added, is Muslim and works in the field of rubber business, which is profitable, so as to create business opportunities for people who want to become rubber entrepreneurs, it is necessary for rubber entrepreneurs to pay zakat maal from selling rubber which can be categorized as zakat commerce or trade. The purpose of this study is to study and analyze how to implement the results of rubber zakat by rubber entrepreneurs in terms of Islamic law and what happens in the implementation of zakat rubber trading by rubber entrepreneurs. Bajubang District has a population of less than 41,513 people, with 72 rubber entrepreneurs from nine villages in Bajubang District. This research is included in the Empirical research conducted Descriptive is research conducted to examine and see the implementation, status and how to determine the ratio of rubber trade zakat by rubber entrepreneurs, In this study primary data and secondary data are used with data collection methods conducted through interviews and literature studies. . The collected data was analyzed qualitatively. The results of this study indicate the implementation of zakat on the results of rubber trade by rubber entrepreneurs and the implementation that occurs in the implementation of zakat on rubber commerce by rubber entrepreneurs Keywords: Rubber; Business; Zakat. Abstrak Di Kecamatan Bajubang mayoritas penduduknya beragama Islam dan bekerja di bidang usaha perkebunan karet bernilai ekonomis tingi yang menguntungkan, sehingga menciptakan peluang usaha bagi orang-orang yang ingin menjadi pengusaha karet, Maka dibutuhkan kesadaran oleh pengusaha karet untuk membayar zakat maal dari penjualan karet yang dapat dikategorikan sebagai zakat perniagaan atau perdagangan. Tujuan penelitian ini untuk mengetahui dan menganalisis bagaimana pelaksanaan zakat hasil perniagaan karet oleh pengusaha karet ditinjau dari hukum islam dan hambatan apa saja yang terjadi dalam pelaksanaan zakat perniagaan karet oleh pengusaha karet. Kecamatan Bajubang jumlah penduduknya kurang lebih berjumlah 41.513 jiwa dengan rincian 72 pengusaha karet dari sembilan desa dikecamatan Bajubang. Penelitian ini termasuk kedalam penelitian Empiris yang bersifat Deskriptif yaitu penelitian yang dilakukan untuk mempelajari dan melihat pelaksanaan, status dan cara menentukan nisab zakat perniagaan karet oleh pengusaha karet, Dalam penelitian ini digunakan data primer dan data sekunder dengan metode pengumpuilan data yang dilakukan melalui wawancaradan studi pustaka. Data yang terkumpul dianalisis secara kualitatif. Hasil dari penelitian ini menunjukkan pelaksanaan zakat hasil perniagaan karet oleh pengusaha karet dan hambatan yang terjadi dalam pelaksanaan zakat perniagaan karet oleh pengusaha karet. Kata kunci:Zakat; Perniagaan; Karet.